Pengembangan Sistem Sliding Adaptive Vertical Pada Proses Pengelasan Smaw Posisi 1G/1F - Windodo Suwanda; Yohanes Yohanes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
This study aims to develop a dynamometer to develop a sliding adaptive vertical engine on SMAW welding with 1G / 1F position. Development of sliding adaptive vertical machine includes design, manufacture, testing of sliding adaptive vertical machine, and testing of welding results with tensile test and penetrant test. The parameters used in this study were using V and fillets, 80 - 90 volts, rotary speed of 44 - 60 rpm stepper motor and 60˚ - 65 sudut electrode angle. Specimen A angle 60˚ - 65˚ current 90 rounds 57 rpm has a tensile strength of 349.91 MPa, whereas specimen B with angle 60˚ - 65˚, current 100 and round 60 rpm has a tensile strength of 304.52 MPa. For the test results using the penetrant showed the specimen C is better than the specimen D.Keywords :Welding, Tensile Strengh, Sliding Adaptive Vertical, SMAW.